2019
DOI: 10.1101/gad.321968.118
|View full text |Cite
|
Sign up to set email alerts
|

Wnt and Notch signaling govern self-renewal and differentiation in a subset of human glioblastoma stem cells

Abstract: Developmental signal transduction pathways act diversely, with context-dependent roles across systems and disease types. Glioblastomas (GBMs), which are the poorest prognosis primary brain cancers, strongly resemble developmental systems, but these growth processes have not been exploited therapeutically, likely in part due to the extreme cellular and genetic heterogeneity observed in these tumors. The role of Wnt/βcatenin signaling in GBM stem cell (GSC) renewal and fate decisions remains controversial. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 47 publications
1
75
0
Order By: Relevance
“…Notch signaling is a fundamental player in the establishment of stem cell fate and behavior in development, regeneration and disease [12][13][14]49]. Notch signaling was shown to be necessary for the maintenance of cancer stem cells in different types of tumors [18,[50][51][52]. As such, it is the target of numerous therapeutic antineoplastic approaches [15,18,53].…”
Section: Discussionmentioning
confidence: 99%
“…Notch signaling is a fundamental player in the establishment of stem cell fate and behavior in development, regeneration and disease [12][13][14]49]. Notch signaling was shown to be necessary for the maintenance of cancer stem cells in different types of tumors [18,[50][51][52]. As such, it is the target of numerous therapeutic antineoplastic approaches [15,18,53].…”
Section: Discussionmentioning
confidence: 99%
“…10 The Notch signaling pathway plays an important role in the maintenance of CSCs 565,566 and can induce CSC differentiation. Abnormal activity of the Notch signaling pathway has been observed in many cancers, such as leukemia, 567 glioblastoma, 568,569 breast cancer, 570 lung cancer, 571 ovarian cancer, 572 pancreatic cancer, 573 and colon cancer. 574 At present, there are three major clinical methods used to inhibit Notch signaling, secretase inhibition (γ-secretase inhibitor (GSI)), Notch receptor or ligand antibodies, and combination therapy with other pathways.…”
Section: Agents Targeting Csc-associated Signaling Pathways In Clinicmentioning
confidence: 99%
“…), suggesting WNT6 and the WNT/β‐catenin signaling pathway as effectors of HOXA9‐mediated aggressiveness in GBM (Costa et al , ; Pojo et al , ). Interestingly, it was recently reported that HOXA genes are part of a gene‐signature characteristic of WNT‐dependent glioma stem cells (Rajakulendran et al , ), which fits well with our data linking HOXA9 and WNT6 in GBM. This link is particularly relevant from a clinical perspective, as it may reveal novel therapeutic opportunities targeting WNT signaling to revert the malignant behaviors of highly aggressive WNT6‐high and HOXA9‐high GBMs, all of which present particularly poor clinical outcome.…”
Section: Discussionmentioning
confidence: 99%